Sequence analysis of the coding regions of the apolipoprotein C2 (APOC2) gene in Miniature Schnauzers with idiopathic hypertriglyceridemia. (November 2020) - Xenoulis, Panagiotis G.; Tate, Nicole M.; Bishop, Micah A.; Steiner, Jörg M.; Suchodolski, Jan S.; Furrow, Eva
Highlights: Causes of idiopathic hypertriglyceridemia in Miniature Schnauzer (MS) are unclear. No variant was found in the coding exons of APOC2 in MS with hypertriglyceridemia. Coding variants in APOC2 are unlikely to be a cause of hypertriglyceridemia in MS. Variants in coding exons of APOC2 were rare in a canine variant database. Whole genome sequencing and/or RNA-Seq analysis might be more appropriate methods. Abstract: It has been hypothesized that idiopathic hypertriglyceridemia in Miniature Schnauzers is hereditary, but the gene responsible has yet to be identified. The objective of this study was to determine if there were coding variants in the apolipoprotein C2 ( APOC2 ) gene in Miniature Schnauzers with idiopathic hypertriglyceridemia. Blood samples from 12 Miniature Schnauzers with idiopathic hypertriglyceridemia were analyzed. Genomic DNA was extracted from whole blood, and the three coding exons of APOC2 were amplified by PCR. The PCR amplicons were sequenced and analyzed for variants relative to the canine reference genome (CanFam3.1 assembly). A second objective was to determine the extent of variation in coding exons of APOC2 in a large and diverse canine population using the Dog Biomedical Variant Database Consortium variant catalog, comprised of whole genome sequencing variant calls from 582 dogs of 126 breeds and eight wolves. There were no variants detected in the coding exons of APOC2 for any of the 12 Miniature Schnauzers with idiopathic hypertriglyceridemia. Variants in the coding exons of APOC2 were also rare in the Dog Biomedical Variant Database Consortium variant catalog; a single synonymous variant was identified in a heterozygous state in a Tibetan Mastiff. Thus, we concluded that coding variants in APOC2 are unlikely to be a major cause of idiopathic hypertriglyceridemia in North American Miniature Schnauzers and furthermore, that such coding variants are rare in the canine population.